Scientific Inquiry in Social Work - DeCarlo, Matthew (Open textbook library., 2018)
As an introductory textbook for social work students studying research methods, this book guides students through the process of creating a research project. Students will learn how to discover a researchable topic that is interesting to them, examine scholarly literature, formulate a proper research question, design a quantitative or qualitative study to answer their question, carry out the design, interpret quantitative or qualitative results, and disseminate their findings to a variety of audiences. Examples are drawn from the author's practice and research experience, as well as topical articles from the literature. There are ancillary materials available for this book.